2018
DOI: 10.1177/0267323117750697
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Scandinavian telecom companies’ corruption in Uzbekistan: The role of investigative journalists

Abstract: Transparency International's yearly Corruption Perceptions Index ranks Scandinavia as one of the least corrupt regions in the world. However, during the past decades, large Scandinavian corporations in the telecommunications, oil and defence industries have-in their struggle for business contracts in other countries-been involved in several large-scale bribery scandals. There has also been a growing range of corruption cases in the Swedish and Norwegian public sectors. In many of these cases, investigative jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Together with these visible effects, media reporting has also had equally important indirect effects thanks to the role it plays in society ( [30], pp. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with these visible effects, media reporting has also had equally important indirect effects thanks to the role it plays in society ( [30], pp. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Pollack and Allern investigated the work of and methods used by investigative journalists in revealing large-scale corruption related to the expansion of Nordic telecom companies in Uzbekistan. They found that investigative journalists have played a crucial role in the disclosure of corruption, sometimes cooperating across media organizations and countries, demonstrating the importance of journalism as a public good for democracy [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…I conducted one telephone interview with Ekeberg to retrieve more details from the investigative work. Moreover, the work of Gottschalk (2018) and Allern and Pollack (2018) offer the necessary recap of the Telenor/VimpelCom case, along with the articles printed in Dagens Naeringsliv in 2012 and Klassekampen in the autumn of 2014.…”
Section: Collaboration In Investigating the Global Economy: Methodological Reflectionsmentioning
confidence: 99%
“…Quality journalism can amplify popular opinion, improve the depth and range of political decision-making and discipline abuse of power. These are among the positive externalities of high-grade journalism (Møen, cited in Allern & Pollack, 2018). On the other hand, Allern and Pollack emphasize the fact that the lack of investigative journalism and the success of superficial, sensationalized journalism make it easier to cover up malpractice and crime in economic and political life (Allern & Pollack, 2018, p. 3).…”
Section: Introductionmentioning
confidence: 99%
“…14 See Søreide 2016, Chapter 3 for examples from OECD countries. 15Pollack and Allern (2018) point out this concern with reference to the telecom sector. For cases of financial secrecy, seeShaxson (2011), andSchjelderup (2016).…”
mentioning
confidence: 99%